Validity and reliability of the Chinese version of the core extrusion schema-revised for high school students in China - Lei, Fei; Chen, Yue; Lei, Shulan; Wang, Dacheng; Zhu, Zhuohong; Li, Xinying; Chen, Jing (Frontiers in Psychology, 2023)
Objective: This study evaluated the validity and reliability of the Chinese version of the Core Extrusion Schema-Revised (CES-R) for assessing high school students and measures invariance across gender and grade parameters.Methods A sample of 1334 high school students in Wuhan, China, participated in the study for item analysis, internal consistency tests, and measurement invariance tests of the CES-R. Additionally, 1745 high school students in Zhejiang Province, China. provided data for questionnaire validation.The results of the confirmatory factor analysis showed that the two-dimensional model fit the data well (chi-squared discrepancy = 113.989; degrees of freedom = 26; Tucker-Lewis index[TLI] = 0.949; comparative fit index [CFI] = 0.963; standardized root mean square residual = 0.072).The Chinese CES-R scores were positively correlated with both the Adolescent Avoidance and Integration Questionnaire scores (r = 0.63, p < 0.01) and the Adolescent Social Anxiety Questionnaire scores (r = 0.70, p < 0.01). The internal consistency coefficient of the questionnaire was 0.94, and the split-half reliability was 0.90. The factor structure invariance, factor loading invariance, and intercept invariance of the Chinese CES-R across gender and grade groups 2 (ΔCFI < 0.01, ΔTLI < 0.01, ΔRMSEA < 0.01) indicated equivalence across gender and grade groups.The Chinese version of CES-R has good validity and reliability for evaluating high school students and acceptable measurement invariance across genders and grades.